2008
DOI: 10.1088/0957-4484/19/15/155604
|View full text |Cite
|
Sign up to set email alerts
|

The growth of ultralong and highly blue luminescent gallium oxide nanowires and nanobelts, and direct horizontal nanowire growth on substrates

Abstract: We report the growth of ultralong β-Ga(2)O(3) nanowires and nanobelts on silicon substrates using a vapor phase transport method. The growth was carried out in a tube furnace, with gallium metal serving as the gallium source. The nanowires and nanobelts can grow to lengths of hundreds of nanometers and even millimeters. Their full lengths have been captured by both scanning electron microscope (SEM) and optical images. X-ray diffraction (XRD) patterns and transmission electron microscope (TEM) images have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…The Ga 2 O 3 NWs have diameters r50 nm, lengths up to 10 mm and exhibited peaks in the XRD corresponding to b-Ga 2 O 3 as shown in Fig. 3(b) [33]. No nanostructures were obtained for T G o800 1C due to the fact that Ga has a low melting point of 29.8 1C together with an unusually high boiling point of 1983 1C and high surface tension, hence a low vapor pressure even at temperatures of a few hundreds 1C.…”
Section: Resultsmentioning
confidence: 99%
“…The Ga 2 O 3 NWs have diameters r50 nm, lengths up to 10 mm and exhibited peaks in the XRD corresponding to b-Ga 2 O 3 as shown in Fig. 3(b) [33]. No nanostructures were obtained for T G o800 1C due to the fact that Ga has a low melting point of 29.8 1C together with an unusually high boiling point of 1983 1C and high surface tension, hence a low vapor pressure even at temperatures of a few hundreds 1C.…”
Section: Resultsmentioning
confidence: 99%
“…As evident from the SEM and TEM images, the Ga 2 O 3 nanorods do not have any catalyst at the tip, indicating that the growth is not through a VLS mechansim. [30,31] We suggest a mechanism in which nanorods are obtained by the nucleation, coalescence, evaporation, and condensation of Ga 2 O 3 particles that are formed initially in the growth process. After heating the molten Gallium in a quartz boat at 1300 8C for 1 h, sub-micrometer-sized irregularly shaped particles and short nanorods are formed (Fig.…”
mentioning
confidence: 96%
“…In another study, Kuo and Huang [58] have reported the growth of ultra-long Ga 2 O 3 nanowires and nanobelts using CVD technique. The length of nanostructures was in sub-millimeter or millimeter range.…”
Section: Growth Of Gallium Oxide Nanostructuresmentioning
confidence: 99%
“…The constant supply for Ga vapours for extended hours and residual oxygen present in the growth chamber played a crucial role in the growth of extra-long Ga 2 O 3 nanostructures. Two silicon [57,58] substrates coated with gold catalyst were placed in the growth chamber at two different places. One substrate (position-1) was directly placed on the Ga source and second a substrate (position-2, 3-5 mm from the Ga source) was placed downstream direction near to the Ga source.…”
Section: Growth Of Gallium Oxide Nanostructuresmentioning
confidence: 99%